Thermally conductive thin films derived from defect free graphene-natural rubber latex nanocomposite: preparation and properties - George, Gejo; Sisupal, Suja Bhargavan; Tomy, Teenu; Pottammal, Bincy Akkoli; Kumaran, Alaganandam; Suvekbala, Vemparthan; Gopimohan, Rajmohan; Sivaram, Swaminathan; Ragupathy, Lakshminarayanan (Carbon, 2017)
Commercially useful rubber products viz. gloves, condoms, tyres, and rubber hoses used in high temperature environments, etc., require efficient thermal conductivity, which increases the lifetime of these products. Graphene can fetch this property, if it is effectively incorporated into the rubber matrix. The great challenge in preparing graphene-rubber nanocomposites is formulating a scalable method to produce defect free graphene and its homogeneous dispersion into polymer matrices through an aqueous medium. Here, we used a simple method to produce defect free few layer (2-5) graphene, which can be easily dispersed into natural rubber (NR) latex without adversely affecting its colloidal stability. The resulting new composite showed large increase in thermal conductivity (480-980%) along with 40% increase in tensile properties and 60% improvement in electrical conductivity. This study provides a novel and generalized approach for the preparation of graphene based thermally conductive rubber nanocomposites. (C) 2017 The Authors. Published by Elsevier Ltd.